Tinjauan Yuridis Penerapan Asas Legalitas Dalam Tindak Pidana Pencurian - Dastin Darmawan; Nur Ain Saputri; Muhammad Irwandi; Yesyka Yesyka (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This journal discusses the application of the principle of legality in criminal law, especially in the crime of theft. The principle of legality is an important principle in criminal law, which states that no act can be punished except on the basis of pre-existing statutory regulations. This journal explains several important implications of the principle of legality, namely: 1) protecting individuals from abuse of power by authorities; 2) demand clear and definite provisions in the criminal law; and 3) guarantee the application of criminal law prospectively, meaning that criminal law cannot be applied retroactively. Furthermore, this journal also discusses developments in regulating the principle of legality in the Draft Law on the Criminal Code (RUU KUHP) which is currently being discussed in the DPR.